Adolescent age moderates genetic and environmental influences on parent–adolescent positivity and negativity: Implications for genotype–environment correlation. (30th April 2015) - Marceau, Kristine; Knopik, Valerie S.; Neiderhiser, Jenae M.; Lichtenstein, Paul; Spotts, Erica L.; Ganiban, Jody M.; Reiss, David
Abstract: We examined how genotype–environment correlation processes differ as a function of adolescent age. We tested whether adolescent age moderates genetic and environmental influences on positivity and negativity in mother–adolescent and father–adolescent relationships using parallel samples of twin parents from the Twin and Offspring Study in Sweden and twin/sibling adolescents from the Nonshared Environment in Adolescent Development Study. We inferred differences in the role of passive and nonpassive genotype–environment correlation based on biometric moderation findings. The findings indicated that nonpassive gene–environment correlation played a stronger role for positivity in mother– and father–adolescent relationships in families with older adolescents than in families with younger adolescents, and that passive gene–environment correlation played a stronger role for positivity in the mother–adolescent relationship in families with younger adolescents than in families with older adolescents. Implications of these findings for the timing and targeting of interventions on family relationships are discussed.